THE EFFECTIVENESS OF THE APPLICATION OF MODERN TECHNOLOGIES IN PEDIATRIC SCIENCE - Tuymamatova Mohira Muradullaevna (Journals Park Publishing, 2023)
This article explores the impact of modern technologies on pediatric science, emphasizing their effectiveness in various aspects of healthcare. It discusses how telemedicine, artificial intelligence, wearable devices, and precision medicine have transformed pediatric healthcare, leading to improved diagnostics, personalized treatment, and enhanced patient care. The article highlights the benefits of integrating these technologies and provides insights into their potential for future advancements in the field.
Keywords: Pediatric science, modern technologies, healthcare, medical advancements, telemedicine, artificial intelligence, wearable devices, precision medicine.